2017
DOI: 10.1117/1.nph.4.4.041410
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cerebral autoregulation in pediatric extracorporeal membrane oxygenation associated with neuroimaging abnormalities

Abstract: Abstract. Extracorporeal membrane oxygenation (ECMO) is a life-supporting therapy for critically ill patients with severe respiratory and/or cardiovascular failure. Cerebrovascular impairment can result in hemorrhagic and ischemic complications commonly seen in the patients supported on ECMO. We investigated the degree of cerebral autoregulation impairment during ECMO as well as whether it is predictive of neuroimaging abnormalities. Spontaneous fluctuations of mean arterial pressure (MAP) and cerebral tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…, ~50% of neonates with ‘normal’ ultrasounds have abnormal MRI post-ECMO ( 20 ). Although a few studies have used oxygen saturation to investigate cerebral perfusion ( 6 8 ), there is limited understanding of adequate cerebral perfusion during ECMO ( 10 , 21 ) or Page 7 of 33 the normative blood pressure range of CA ( 9 ). DCS and FD-DOS are promising tools to address these needs.…”
Section: Introductionmentioning
confidence: 99%
“…, ~50% of neonates with ‘normal’ ultrasounds have abnormal MRI post-ECMO ( 20 ). Although a few studies have used oxygen saturation to investigate cerebral perfusion ( 6 8 ), there is limited understanding of adequate cerebral perfusion during ECMO ( 10 , 21 ) or Page 7 of 33 the normative blood pressure range of CA ( 9 ). DCS and FD-DOS are promising tools to address these needs.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients on ECMO exhibit disturbances in cerebral autoregulation (17), which is the brain’s ability to maintain constant CBF despite changes in systemic blood pressure (18). Continuous near-infrared spectroscopy bedside monitoring can identify disrupted cerebral autoregulation for several diseases associated with secondary neurologic injury, including ECMO (17, 19, 20). In our patient population, 13 patients were simultaneously enrolled in an observational study to monitor cerebral autoregulation over the course of ECMO, including six ECMO patients without brain injury, and seven with acquired brain injury.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time, we show in this pilot study that pediatric ECMO results in the loss of cerebral autoregulation concomitant with a robust mobilization and activation of adaptive immune cells, detection of CNS-targeting adaptive immune responses, and induction of pro-inflammatory cell signaling predominantly in patients that present with acquired brain injury. We previously reported that acquired brain injuries could be predicted by loss of cerebral autoregulation in pediatric ECMO patients (17). What is critical to consider is that as cerebral autoregulation is disrupted, the blood flow in the brain is no longer constant but fluctuates similar to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cerebral blood flow rate and volume can contribute to altered cerebral oxygenation as demonstrated by cerebral oximetry [12]. Impairments in cerebral autoregulation, based on wavelet transform coherence, are associated with findings on neuroimaging and neurologic outcomes [16].…”
Section: Cerebral Blood Flow and Oxygenation On Ecmomentioning
confidence: 99%